Relationships of emotion regulation to procrastination, life satisfaction and resilience to discomfort - Manuel González; Anna Rovella; Andrea Barrera; Mario González (Interacciones)
Background: Emotion regulation involves the modulation of emotional experiences to facilitate goal attainment. Conversely, emotional difficulties are a pattern of emotional experiences and expressions that interfere with goal-directed behavior. Objectives: Our aim was to determine the relationship between emotional regulation difficulties with procrastination, life satisfaction, and resilience to distress. Methods: The sample consisted of 366 individuals from the general population, with a mean age of 33 years (SD=15) and 62.1% female. Results: Procrastination was positively related to the six emotional distress regulation strategies and negative affect (NA), and negatively related to positive affect (PA). Life satisfaction and distress endurance are negatively related to the identified regulation strategies and NA, and positively related to PA. Procrastination, once NA and PA are controlled is predicted by lack of clarity and lack of goals. Satisfaction with life and resistance to distress are predicted by less lack of strategies. Conclusions: It is concluded that of the sociodemographic variables only age is relevant to procrastination, given that people younger than 21 years score higher on this construct. Procrastination is positively related to the six dimensions of difficulties in emotion regulation, where it is predicted by lack of goals and lack of clarity, however, satisfaction with life and resistance to discomfort by less lack of strategies.